Sistematização das evidências empíricas em desenvolvimento distribuído de software - Techio, Antônio Rafael da Rosa (2014)
Distributed Software Development (DSD) is a recent area and has been growing over the last few years. As a result, a quite number of research and industrial studies have been published. However, due to the large number of terms involved in this scenario, a concept is often used wrongly, making the process of searching for empirical evidence a complex task. The DSD scenarios are diverse and what works in one context might not directly apply in another. Thus it is necessary to understand how DSD related empirical findings should be reported to be useful for practitioners and researchers. Empirical research in DSD could be refined if there was a systematic way to identify the different dimensions and characteristics for which empirical evidence applies. For this reason, the goal of this dissertation is to identify the type of context information that is relevant to researchers and practitioners in studies with empirical evidence and propose a way to systematize the empirical evidence in DSD, in order to contribute, among other things, to the future development of research in the area. For the development of this research we have used both secondary (systematic mapping study) and primary (expert opinion survey) research methods. The main contribution of this research is the taxonomy to systematize the empirical evidences generated from scientific research conducted in the DSD area.